Main street revitalization effort for the village of Union, Nebraska - Cox, Taylor A. (Kansas State University, 2013)
Rural communities across America are working to strengthen their economies, provide better quality of life to residents, and build on assets such as traditional main streets, transportation initiatives, and natural amenities and resources. Today, rural communities face an array of challenges. Small communities are vulnerable to the impacts of expensive commutes, lack of mobility, financial resources, and other services. According to the USDA, “Some small communities, have limited local government staff, experience, or funding, which can mean few resources dedicated to providing sustainable amenities, regional collaboration, and other efforts to identify shared community goals and visions that can help shape growth and development” (USDA, 2011). Small communities must work hard to compete with larger cities and other communities to sustain economically and become prominent. This is often noticeable when there is a lack of investment and economic prosperity. Many rural communities have limited transportation options. Most small communities are not fit to support multiple modes of transportation, which limits access to jobs, medical care, and educational opportunities. For those who do drive, commutes to distant employment centers can be time consuming and require a large percentage of the family budget to be spent on transportation (USDA, 2011). In addition, intercity and regional mobility are drivers of economic growth in rural communities and bring tourists and other consumers to community businesses. Rural communities and small towns should be valued for their distinctive and historic features. Communities that conserve and build upon these resources, such as historic downtowns and main streets, will be better positioned to enhance quality of life for their residents. Without revitalizing main streets we would not see the places of shared memory where people are suppose to come together to live, work, and play.
Keywords: Transportation Planning; Main Street; Sustainability; Economic Development; Brownfield Remediation; Revitalization; Area Planning and Development (0341); Sustainability (0640); Transportation (0709)